Optimasi Pendidikan Kewarganegaraan Berbasis Community Civic dalam Memperkuat Literasi Mitigasi Bencana Masyarakat di Sekitar Sesar Lembang - Nanggala, Agil; Rostika, Deti; Mulyati, Tita; Muna Aljamaliah, S. Nailul; Mujahidillah Adzimat Sukmayadi, Qolbi; Samrotul Fuadah, Intan; Fitriani, Feni (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This research aims to optimize community-civic-based Civics Education (PKn) to strengthen disaster mitigation literacy among communities near the Lembang Fault, thereby making the subject—within its socio-cultural scope—more comprehensive and impactful in society. Employing a qualitative approach via a literature review, the study utilizes data analysis techniques comprising data condensation, data display, and verification. The findings indicate that: 1) Community-civic-based Civics Education is highly relevant and can be optimized to strengthen disaster mitigation literacy in communities near the Lembang Fault, as it incorporates socio-cultural dimensions, civic engagement, civic literacy, and civic virtue—serving as social capital to foster community resilience against various disasters; and 2) The practice of community-civic-based Civics Education accommodates